1997
DOI: 10.1074/jbc.272.21.13843
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning and Expression of a Novel UDP-N-acetyl-d-galactosamine:PolypeptideN-Acetylgalactosaminyltransferase

Abstract: The cDNA for a fourth member of the mammalian UDP-GalNAc:polypeptide N-acetylgalactosaminyltransferase family, termed ppGaNTase-T4, has been cloned from a murine spleen cDNA library and expressed transiently in COS7 cells as a secreted functional enzyme. Degenerate primers, based upon regions that are conserved among the known mammalian members of the enzyme family (ppGaNTase-T1, -T2, and -T3) and three Caenorhabditis elegans homologues (ppGaNTase-TA, -TB, and -TC), were used in polymerase chain reactions to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
137
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 18 publications
2
137
1
Order By: Relevance
“…1, panel L). Since GalNAc-T1 transfers GalNAc to Thr 1 , Thr 9 , and Ser 20 in isolated experiments (Fig. 1, panel H), it is concluded that GalNAc-T4 transfers to Ser 10 in -VTSAand Thr 14 in -PDTR-.…”
Section: Galnac-t4 Transfer To At Least Three Sites In the Muc1mentioning
confidence: 86%
“…1, panel L). Since GalNAc-T1 transfers GalNAc to Thr 1 , Thr 9 , and Ser 20 in isolated experiments (Fig. 1, panel H), it is concluded that GalNAc-T4 transfers to Ser 10 in -VTSAand Thr 14 in -PDTR-.…”
Section: Galnac-t4 Transfer To At Least Three Sites In the Muc1mentioning
confidence: 86%
“…The finding that GalNAc-T3 expression was retained more frequently in nonsquamous cell carcinomas (most of which were adenocarcinomas) than in squamous cell carcinomas may reflect tissue specific expression of GalNAc-T3 in organs that contain secretory epithelial glands (Hagen et al, 1993; Homa et al, GalNAc-T3 expression in NSCLCs H Dosaka-Akita et al 1993; White et al, 1995;Bennett et al, 1996). Moreover, in nonsquamous cell carcinomas, decreased expression of GalNAc-T3 was associated with unfavourable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Each oligosaccharide is synthesised by a specific glycosyltransferase (Varki, 1993). The initial glycosylation of mucin-type O-linked proteins is catalysed by one of the UDP-N-acetyl-a-D-Galactosamine: polypeptide Nacetylgalactosaminyl transferases (GalNAc-transferase family of enzymes) (Hagen et al, 1993;Homa et al, 1993;Wandall et al, 1997;). Three distinct human GalNAc-transferases, GalNAc-T1, GalNAc-T2, and GalNAc-T3, have been characterised (White et al, 1995;Bennett et al, 1996;Wandall et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions were carried out at 378C in 25-ml mixture containing 500 mM gp 120 or EA2 peptides and 51 mM UDP-[ 14 C]GalNAc (7.8 mCi/mmol, PerkinElmer Life Sciences, Waltham, MA, USA) in 10 mM MnCl 2 , 40 mM sodium cacodylate (pH 6.6), 40 mM b-mercaptoethanol, and 0.1% Triton X-100 as described. (24) The reactions were initiated by adding 12.5 mg total cell extract protein for each sample. Reactions with cell extracts were carried out in the presence of 20 mM CDPcholine to inhibit endogenous non-ppGalNAcT-mediated hydrolysis activity.…”
Section: Cytoimmunochemistry and Laser Confocal Microscopymentioning
confidence: 99%